UTILIZATION OF CHITOSAN PREPARED FROM SHRIMP SHELL AS FAT DILUENT - Hargono Hargono; M. Djaeni (JOURNAL OF COASTAL DEVELOPMENT, 2003)
Shrimp shell waste from seafood restaurants and canned shrimp industries is potential to be used as chitosan source. This material contains 18.1% of chitin which could be converted into chitosan through demineralization, deproteination and deacetylation process. Chitosan is fine chemical used to adsorb fat from body, heavy metal absorbent, fat diluent and medicine. This research looked into the prospect of chitosan from shrimp shell as fats dilluent. The aims of this research are to study the influence of NaOH concentration on preparing chitosan from shrimp shell, and evaluate the performance of chitosan produced as fat diluent. As indicators, the purity of chitosan and the percentage of fats diluted are measured. This investigation was conducted in two steps involving the preparation of chitosan and the process optimation of fats dillution using chitosan. In this case, the NaOH concentration was varied from 20% to 60% with the step size of 10% to obtain highest quality of chitosan. Whereas, in the second step, the time of fats dilution and chitosan quality were varied to obtain optimum condition of fats dillution. The dillution time was varied from 10 to 30 minutes with incremental of 5 minutes. While, the chitosan quality was varied based the result of preparation step. The results indicated that the highest chitosan quality of 82.45% could be obtained in the percentage of NaOH of 60%. Meanwhile, in the fats dillution process, it showed that the highest percentage of fats dilluted is 96.57% that could be achieved at time dillution of 10 minute and chitosan quality of 82.45%.